A comparative study of low concentration of levobupivacaine versus ropivacaine with fentanyl for patient-controlled epidural labour analgesia - Priyanka Chuttani; Udeyana Singh; Anju Grewal; Sunil Katyal; Ashima Kaura (Wolters Kluwer Medknow Publications, 2018)
>Background and Aims: Lumbar epidural analgesia is considered the modality of choice for labour analgesia. Despite its super analgesia and improved safety profile, it has been associated with maternal adverse effects like higher incidence of instrumental assisted vaginal delivery (AVD) and motor block leading to decreased ambulation. This study was designed to evaluate the efficacy of low concentrations of local anaesthetics (0.1% ropivacaine and 0.1% levobupivacaine) with 2 μg/ml fentanyl as a patient controlled epidural analgesia (PCEA) technique on the incidence of instrumental AVD along with evaluation of obstetric, maternal, and foetal outcomes.Materials and Methods: In this prospective study, 60 labouring parturients were randomly allocated into two equal groups to receive either 0.1% ropivacaine with 2 μg/ml fentanyl or 0.1% levobupivacaine with 2 μg/ml fentanyl as epidural solutions via PCEA pump infusions (4 ml/h) after 15 ml loading dose of the respective solutions. The incidence of instrumental AVD was noted as the primary outcome along with demographic data, maternal and foetal vital parameters, maternal VAS scores, degree of motor blockade and total epidural drug consumption.Results: The incidence of instrumental AVD was found to be 43.3% in the levobupivacaine group and 30% in the ropivacaine group. This difference was not statistically significant. Both the groups were comparable in terms of demographic data, maternal VAS scores, total epidural drug consumption and foetal APGAR scores.Conclusion: The use of newer local anaesthetics (levobupivacaine and ropivacaine) in low concentrations with opioids (fentanyl) as a PCEA technique may offer high maternal satisfaction in terms of quality of pain relief with fewer adverse events like instrumental AVD and adverse foetal outcomes.